EVALUATION AND COMPARATIVE ANALYSIS OF THE TYPE OF HEART RATE REGULATION FOR LOAD DETERMINATION IN PHYSICAL CULTURE LESSONS - Mishchenko I.V.; Lebedeva M.P.; Sharenkova L.A.; Smolina V.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the type of heart rate regulation of younger schoolchildren as an indicator of adaptation to school loads, including physical exercises in physical education lessons and in sports sections. Methods and structure of the study. The analysis of heart rate variability in schoolchildren aged 7-10 years was carried out, in which 156 schoolchildren (70 boys and 86 girls) took part. The study was carried out with the apparatus "Varicard" with the software "Integrated system of cardiointervalometry", version 6.2. Indicators of heart rate variability are objective indicators of the tone of the autonomic nervous system (its sympathetic and parasympathetic divisions). They also reflect an assessment of the severity of the body’s adaptive response to external stimuli (training load, physical activity, living conditions, region of residence, weather and other stressors). The functional state was assessed using a 4-point system (4 types of regulation). Results and conclusions. In the age group of 7-8 years, the third type of regulation predominates (moderate predominance of parasympathetic activity). The third type of regulation prevails in both boys and girls. The functional state is very good, the optimal state of the regulatory systems. These schoolchildren are shown physical education classes, motor loads without restrictions. A third of the surveyed schoolchildren in this age group has the first type of regulation, which indicates a moderate tension of regulatory systems. Schoolchildren with the first type of regulation are advised to limit emotional stress, physical education without restrictions. In the age group of 9-10 years, the third type of regulation also prevails in both boys and girls. In the general group, this is 60.5%. In this age group with the first type of regulation, there are twice as many girls as boys. As a result of the study, it was found that 81.4% of schoolchildren aged 7-10 years old can engage in physical education without restrictions. And 18.6% of schoolchildren are shown physical education classes in a health-improving mode.